1990
DOI: 10.1007/bf01957683
|View full text |Cite
|
Sign up to set email alerts
|

Criss-cross heart evaluated by colour Doppler echocardiography and magnetic resonance imaging

Abstract: Two-dimensional colour Doppler echocardiography was performed on a 1-month-old male infant with criss-cross heart, double outlet right ventricle, ventricular septum defect and pulmonary stenosis. Complex structural abnormalities were suspected after two-dimensional echocardiography (2-D echo) and confirmed by colour Doppler and magnetic resonance imaging (MRI). We stress that the blood streams in the ventricular inflow tracts revealed by colour Doppler and the spatial relationships of the cardiac segments disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Postnatal presentation varies and may include cyanosis, heart failure or a murmur, depending on the full sequential diagnosis and associated abnormalities. The diagnosis can be established by echocardiography, angiocardiography and magnetic resonance imaging 9,10 . It appears to be an isolated cardiac finding with no associated extracardiac or chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal presentation varies and may include cyanosis, heart failure or a murmur, depending on the full sequential diagnosis and associated abnormalities. The diagnosis can be established by echocardiography, angiocardiography and magnetic resonance imaging 9,10 . It appears to be an isolated cardiac finding with no associated extracardiac or chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Exceptions include patients with complex anomalies of the aortic arch, pulmonary arteries, aorto-pulmonary collaterals, and systemic or pulmonary venous anomalies that are not completely delineated by echocardiography. Several investigators demonstrated the use of CMR for the assessment of the relationship between the great vessels and the VSD as well as the position of the great vessels in relation to the conal septum (72)(73)(74)(75)(76).…”
Section: Pre-operative Mrimentioning
confidence: 99%
“…This congenital defect was first described by Lev and Rowlatt in 1961, but it was only in 1974 that Anderson et al first used the term crisscross heart. A total of 316 cases of the anomaly have been reported in articles cited in PubMed to date (2016) …”
Section: Discussionmentioning
confidence: 99%
“…Most patients have VSDs, transposition of the great arteries, double‐outlet right ventricle, hypoplastic right ventricle, PS and tricuspid hypoplasia, the latter present in most patients. Other associated defects, although less frequent, are straddling mitral or tricuspid valves, subaortic stenosis, aortic arch obstruction, and mitral stenosis . Anomalies of the coronary circulation may be present and are usually related to the ventricular position, and in these cases, magnetic resonance image (MRI) and angiography are useful tools in the diagnosis and approach .…”
Section: Discussionmentioning
confidence: 99%